REGULATION OF THE RIGHTS OF CHILDREN IN OUT-OFHOME CARE BY TRUSTEE IN LATVIAN AND INTERNATIONAL POLITICS - Vasechko, Lubova (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article provides an analysis of the way in which the Latvian regulatory framework in force determines the fulfilment of the needs of the child in out-of-home care by trustee and stability. This analysis indicates that in Latvian legislation the concept of “interests of the child” has not been clearly stated, in this regard, the Latvian legislation provides information of the rights of the child and the fulfilment of his physical needs. The concept of trustee and the existence of the concept is not mentioned. In contrast, international declarations and conventions on the topic of the protection of the rights of the child are much more humanitarian; in those documents, love and understanding from adults are acknowledged as the primary components in the harmonious development of the personality of the child.